Matt's mitt ; & Fleet-footed Florence - Sachs, Marilyn; Robinson, Charles; Sachs Marilyn 1931 (New York : Dutton, 1989)
In the first of these two baseball stories, the mitt given at Matt's birth by his errant uncle possesses unusual qualities which shape his life. In the sequel, the fleet-footed star of the North Dakota Beavers meets her match when she encounters Yankee catcher, Fabulous Frankie.
Keywords: Baseball; Children's stories American; Short stories; Baseball stories American -- Fiction